Communicating about zoonotic disease: Strategic considerations for wildlife professionals - Daniel J. Decker; William F. Siemer; Margaret A. Wild; Kevin T. Castle; David Wong; Kirsten M. Leong; Darrick T. N. Evensen (Wildlife Society Bulletin)
Abstract A set of interrelated social and environmental changes have accelerated the transmission of wildlife‐associated infectious diseases around the world. Emerging infectious disease (EID) events take a heavy toll on human health and have significant global economic impacts. In the risk‐averse society of the United States, EID events associated with wildlife, particularly zoonoses, have potential to diminish the value of wildlife for society, depress interest in wildlife‐related activities and decrease support for wildlife conservation. Messages about wildlife‐associated zoonotic diseases should promote human and animal health, while avoiding development of exaggerated risk perceptions that can have deleterious effects on participation in wildlife‐related outdoor activities or support for wildlife conservation. We outline 3 categories of negative consequences arising from current communication conditions with respect to zoonoses. We then describe key communication links that the wildlife profession needs to address to obviate these consequences. Finally, we propose a number of actions the wildlife professional community can take to improve communication about zoonotic diseases. In this regard, we discuss the One Health concept and other opportunities for interdisciplinary collaboration on communication between wildlife health, wildlife management, and public health professionals. We conclude that a foundation for effective communication about zoonotic diseases needs to be built on stronger interdisciplinary collaboration between the wildlife profession and the public health profession. Starting from a solid foundation of collaboration among wildlife veterinarians and wildlife biologists and managers, wildlife professionals should build strong bridges with the public health profession. We suggest that the latter can be spanned by wildlife veterinarians. © 2011 The Wildlife Society.